Neurotropic Viruses as Acute and Insidious Drivers of Aging - Angela Rocchi; Hassen S. Wollebo; Kamel Khalili (Biomolecules)
Aging is the result of various compounding stresses that gradually overcome the homeostatic regulation of the cell, resulting in irreversible damage. This manifests as many acute and chronic conditions, the most common of which are neurodegeneration and dementia. Epidemiological studies have shown significant, strong correlations between viral infection and neurodegenerative diseases. This review overlays the characteristics of viral pathogenesis with the hallmarks of aging to discuss how active and latent viruses contribute to aging. Through our contextualization of myriad basic science papers, we offer explanations for premature aging via viral induction of common stress response pathways. Viruses induce many stresses: dysregulated homeostasis by exogenous viral proteins and overwhelmed protein quality control mechanisms, DNA damage through direct integration and epigenetic manipulation, immune-mediated oxidative stress and immune exhaustion, and general energy theft that is amplified in an aging system. Overall, this highlights the long-term importance of vaccines and antivirals in addition to their acute benefits.